Physicians’ views on the usefulness of practical tools for assessing the driving ability of older drivers: a cross-sectional study - Paul Sebo (Family Medicine and Community Health)
Objective We aimed to explore Swiss physicians’ views on the usefulness of a self-administered questionnaire completed by older drivers before the consultation and a reference guide summarising current Swiss guidelines on the fitness-to-drive assessment of older drivers. We also aimed to assess the frequency with which physicians used the information sources provided by the Swiss traffic medicine website.Design Questionnaire-based cross-sectional study.Setting The study was conducted in four cantons of Western Switzerland (Geneva, Vaud, Neuchâtel and Jura).Participants All physicians certified to carry out fitness-to-drive assessments in the canton of Geneva (medical assessors; n=69) and a random sample of 500 general practitioners practising in the cantons of Vaud, Neuchâtel and Jura were invited to participate. They were asked to report their estimated average number of fitness-to-drive assessments per week and to rate on a 5-point Likert scale the perceived usefulness of the preconsultation patient questionnaire and reference guide, and the frequency of use of the information sources provided by the traffic medicine website. We computed the proportion of physicians who found the assessment tools very/somewhat useful and the proportion of physicians who always/often used the traffic medicine website. We compared the responses according to medical specialty (medical assessors vs general practitioners) using design-based F tests and weighted logistic regressions.Results 268 physicians (47%) agreed to participate in the study. Their median number of assessments was 2 per week (IQR 2). Overall, the majority of physicians found the questionnaire (75%) and reference guide (89%) very/somewhat useful. Only 17% of the sample always/often used the traffic medicine website. There were no statistically significant associations in multivariable analysis between the medical specialty and the perceived usefulness of the questionnaire and reference guide and the frequency of use of the traffic medicine website.Conclusion Many physicians find the preconsultation patient questionnaire and reference guide useful to guide them for assessing the driving ability of older drivers, but only a minority regularly use the information sources provided by the traffic medicine website. Future studies should explore the reasons why many physicians do not use these available sources of information.